1984
DOI: 10.1007/bf00226301
|View full text |Cite
|
Sign up to set email alerts
|

Microinjection of RNA polymerase II corrects the temperature-sensitive defect of tsAF8 cells

Abstract: tsAF8 cells are a temperature-sensitive (ts) mutant of BHK cells that arrest in the G1 phase of the cell cycle at the non-permissive temperature of 40.6 degrees C. Previous reports had suggested that the temperature-sensitivity of these cells was based on a defect in either the synthesis, assembly or turnover of RNA polymerase II. We now show that the direct microinjection of purified RNA polymerase II into nuclei of tsAF8 cells corrects the ts defect and allows these cells to enter the S phase of the cell cyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

1984
1984
1993
1993

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…This corresponds to early-to-mid G1 for these cells. After selection for poly(A)+ mRNA, 1.4 ,ug of double-stranded cDNA with an average size of 800 base pairs was synthesized from 5 ,ug of RNA. The cDNA was inserted into the tetracycline-resistance gene of pBR322 at the BamHI site after digestion with Sau3A1 to an average of 250-300 base pairs.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This corresponds to early-to-mid G1 for these cells. After selection for poly(A)+ mRNA, 1.4 ,ug of double-stranded cDNA with an average size of 800 base pairs was synthesized from 5 ,ug of RNA. The cDNA was inserted into the tetracycline-resistance gene of pBR322 at the BamHI site after digestion with Sau3A1 to an average of 250-300 base pairs.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, it has been demonstrated that a G1-specific temperature-sensitive mutant, tsAF8, which arrests in G1 at the restrictive temperature (2), is a mutant of RNA polymerase II (3)(4)(5)(6). In addition, the progression of cells in culture through G1 can be inhibited by the intracellular microinjection of a-amanitin (5), a drug that at low concentrations is known to have one and only one specific site of action, the large subunit of RNA polymerase II (7).…”
mentioning
confidence: 99%
“…The other example of G1 arrest caused by a mutation in the general transcriptional machinery is an RNA polymerase II mutant (Burstin et al 1974;Waechter et al 1984).…”
Section: How Does the Ccg1 Mutant Cause G1 Arrest?mentioning
confidence: 99%
“…The expression of particular genes during the GI phase of the mammalian cell cycle is required for the commitment of the cell towards division (3,4,40). Genes that possess the characteristic of enhanced expression when quiescent cells in culture are stimulated to proliferate by mitogens therefore constitute an interesting class in which functions that are essential for cell proliferation may be sought.…”
mentioning
confidence: 99%